Facilitation interaction in distance education of pedagogical universities - Prokopenko , I. (New Collegium, 2020)
The article is devoted to one of the current problems in pedagogy – the implementation of facilitation interaction in distance education of pedagogical universities. The analysis of the literature showed that Ukrainian professional educational organizations in more than 50% of cases use the educational platform Moodle, which allows to implement individual learning direction of students, create a single user interface for all participants in the learning process, while actively using forums, glossaries, automatic interactive testing, etc., focused on the implementation of optimal facilitation interaction of the subjects of the educational process, taking into account the specifics of the pedagogical university. In the article the essence of the concept of «facilitation interaction» is defined as subject-subject interaction, within which pedagogical support and initiation of various forms of activity of students of pedagogical universities at all stages of the educational process, within which personal formation and development every future teacher as a subject of educational and professional activity. Based on the analysis of scientific papers and taking into account the specifics of the organization of distance education at the Pedagogical University, the main tasks in the implementation of facilitation interaction at a distance are: technical understanding and experience of using online tools by the teacher-facilitator; anticipate and possibly adjust online tools to really make it easier for participants to work interactively and engagingly (during skype / zoom / meet communication). In the course of the research it was proved that the facilitator must master the skills – to create the effect of inclusion and presence here and now, regardless of time zones, cultural differences, sometimes – language, to ensure facilitation interaction in distance education.